ANALISIS FAKTOR DALAM PENGAMBILAN KEPUTUSAN NASABAH MEMILIH PRODUK PEMBIAYAAN PERBANKAN SYARIAH (Studi Kasus Pada PT Bank Syariah Mandiri Cabang Ciputat) - Zainuddin, Zulkifli (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2016)
Redundant submitting by the author, this article retracted by Editor--This study aims to determine (a) the factors that influence a client's decision to choose the financial products and (b) Which factors most dominant influence a client's decision in choosing financing in PT Bank Syariah Mandiri Branch Ciputat. The population in this study are all people who have a business in Ciputat and customers who visit the Bank Syariah Mandiri Branch Ciputat to finance. Convenience sampling method selected 100 of the people who have businesses and customers who visited the Bank Syariah Mandiri Branch Ciputat. Test analysis used in this study is to test the factor analysis. Tthis study show that (a) the factors that influence a client's decision in choosing a loan product Bank Syariah Branch Ciputat consists of five factors formed and (b) the most dominant factor influencing the customer's decision in choosing a loan product Bank Syariah Branch Ciputat is factor process (X7). Keywords: Keputusan nasabah, bauran pemasaran jasa, ekuitas merek, karakteristik dan perilaku nasabah--Redundant submitting by the author, this article retracted by Editor--